Body Beautiful : studies in masculine art. (London : Weider Publications.)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : 60 Greek Street, London W1; vanaf 04(1958-1959) : Male Classics, 6-10 Lexington Street, London W1; vanaf (1961) : Body Beautiful Ltd., 15 Kensington High Street, London W8
Engels
Periodiek